'What's up with ur emotions?' Untangling emotional user experience on Second Life and Facebook. Issue 1 (2nd January 2023) - Photiadis, Thomas; Papa, Venetia
ABSTRACT: Online social environments continue to be expanded in human's life and transmuted as representative tools of people's experiences affecting their online and offline emotional behaviour and attitude. There is, nonetheless, an empirical gap regarding the role of the intrinsic emotional fluctuations in social platforms and their effect on self-disclosure behaviour, reflecting information to self-reports. The current study aims an in-depth understanding of an 'outdated' online social environment (Second Life) with a contemporary one (Facebook), based on users' emotional behaviour and approaches. The study's overarching aim is to determine the self-disclosure behaviour through Second Life and Facebook, thus investigating the highlighted emotional experience and providing insights for understanding the progression of enhancing online well-being. The empirical study was conducted, by implementing explanatory mix methods to achieve the study's objectives. Self-disclosure behaviour can shed light on how emotional responses might be used in other social media platforms by opening up the discussion for further exploration [in line with Pentina and Zhang (2017). "Effects of Social Support and Personality on Emotional Disclosure on Facebook and in Real Life." Behaviour & Information Technology 36 (5): 484–492.]. This experiential perspective can be utilised across multiple fields such as HCI, media psychology, well-being technology, UX, user-centred design, social and human aspects in the digital world, and the body of knowledge on engagement in online social environments.